The Role of Partnerships and Business Networks in the Growth of MSMEs in the Digital Age - Sutrisno, Sutrisno (Technology and Society Perspectives (TACIT), 2023)
MSMEs have proven their vital role as economic pillars in various countries around the world. MSMEs have now transformed a lot. Major changes in the business landscape brought about by the digital age have also affected MSMEs. In fact, partnerships and business networks offer the potential to help MSMEs overcome the challenges they face. This study aims to examine the role of partnerships and business networks in the growth of MSMEs in the digital era. This research is a literature review using a qualitative approach, which means that it will analyse and interpret data using information and text from different sources. The study results show that the role of partnerships and business networks in the growth of MSMEs in the digital era is very important. Partnerships with large enterprises and other MSMEs allow MSMEs to expand access to markets and resources, while business networks help them connect with other business actors, increase visibility and provide collaboration opportunities. However, the success of these partnerships and networks depends on easy access to information technology and digital infrastructure.